Pendekatan Teknik Sosial dalam Edukasi DAGUSIBU untuk Peningkatan Kesehatan Masyarakat Desa Donggala - Akbar, Muhammad Hajar; Rianti; Ramadani; Cahya Wulandari, Devita Sari; Akbar; Ilcham (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2025)
The DAGUSIBU (Obtain, Use, Store, Dispose) medication counseling and education program in Donggala Village, Wolo District, Kolaka Regency, aims to enhance community knowledge and awareness of proper medication use. This initiative is motivated by the low level of public understanding regarding medication management, which often negatively impacts individual and environmental health. The program employs a participatory approach, involving lectures, discussions, simulations, and Q&A sessions, supported by a mixed-method research design combining qualitative and quantitative approaches. The results showed a significant increase in participants' understanding after the counseling, particularly in obtaining medications from official sources and using medications according to medical guidance. Direct practice simulations proved effective in facilitating behavioral change. Despite challenges such as varying levels of health literacy, the program successfully encouraged positive changes in daily medication use and highlighted the importance of continuous education. The DAGUSIBU education model can be applied in other areas to foster healthier and more responsible medication management practices within communities.